2008
DOI: 10.1258/jms.2008.007036
|View full text |Cite
|
Sign up to set email alerts
|

High-grade cervical abnormalities and screening intervals in New South Wales, Australia

Abstract: Objectives This study aims to determine the association of two versus three year screening intervals with the likelihood of detection of a high-grade cervical abnormality and cervical cancer. Methods Data were obtained from the New South Wales (NSW) Papanicolaou (Pap) Test Register (PTR) and NSW Central Cancer Registry (CCR). Subjects were human papillomavirus (HPV) unvaccinated women aged 20-69 years who had a minimum of two Pap tests with a negative result at their first recorded Pap test (n ¼ 1,213,295). Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This is likely to be due to the longer screening interval allowing a greater fraction of high grade cases to regress naturally, whilst maintaining a similar detection rate for those high grade lesions that would have progressed to invasive cervical cancer. Our prediction of a reduced number of high grade treatments in the National Cervical Screening Program is broadly consistent with the findings of a prior analysis of NSW registry data, which predicted a statistically non-significant decrease in histologically-confirmed high grade cases, and a significant decrease in rates of high grade cytology, in the context of 3-yearly screening [19]. However, the estimates from this prior study are not directly comparable to the current evaluation because we considered the overall effects of lifetime screening behaviour in the entire population; whereas the prior study estimated the increased risk of a high grade according to screening interval in women with 2 or more cytology tests (conditional on the first test having a negative result), and applied these estimates by pro-rating the 2-yearly participation rate to a 3-yearly situation.…”
Section: Discussionsupporting
confidence: 88%
“…This is likely to be due to the longer screening interval allowing a greater fraction of high grade cases to regress naturally, whilst maintaining a similar detection rate for those high grade lesions that would have progressed to invasive cervical cancer. Our prediction of a reduced number of high grade treatments in the National Cervical Screening Program is broadly consistent with the findings of a prior analysis of NSW registry data, which predicted a statistically non-significant decrease in histologically-confirmed high grade cases, and a significant decrease in rates of high grade cytology, in the context of 3-yearly screening [19]. However, the estimates from this prior study are not directly comparable to the current evaluation because we considered the overall effects of lifetime screening behaviour in the entire population; whereas the prior study estimated the increased risk of a high grade according to screening interval in women with 2 or more cytology tests (conditional on the first test having a negative result), and applied these estimates by pro-rating the 2-yearly participation rate to a 3-yearly situation.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we could not identify the history of cervical cancer screening among our study subjects. Previous studies have reported that socioeconomic status is highly significantly negatively associated with a longer screening interval [49], [50]. In addition, screening interval has been shown to be significantly positively associated with a cytological prediction of diagnosis [10], [49].…”
Section: Discussionmentioning
confidence: 89%
“…In our paper ‘High-grade cervical abnormalities and screening intervals in New South Wales, Australia‘ 1 we estimated the number of extra cases of high-grade cervical abnormality annually if the screening interval policy in New South Wales were to be changed from two to three years as 267 by cytology and 225 by histology, assuming the same number of women participated triennially as biennially. These estimates were based on modelled increased risk of a high-grade lesion with a three-year versus two-year screening interval of OR = 1.36 (95% CI:1.28–1.44) for cytology and OR = 1.47 (95% CI:1.36–1.58) for histology, and also on pro-rating the existing two-yearly screening rate to three-yearly.…”
Section: Correction To Article Published In March 2008mentioning
confidence: 99%